Role of Dynamic Capabilities in the Performance of Manufacturing Firms in Nairobi County, Kenya - Thomas O. Nyachanchu; Joel Chepkwony; Ronald Bonuke (European Scientific Journal, ESJ, 2017)
The advent of globalization has brought with it drastic changes to the operating landscape for firms in the manufacturing sector. The need for transformational changes so as sustain competitive advantage has been on  the rise. Firms are expected to continuously re-engineer their business models and operations to catch up with the turbulent environment. Previous studies have investigated the contribution of manufacturing firms in economic growth. Some have concentrated on the preferred approaches that countries should take, whether protectionism or free market. However, empirical studies investigating direct impact of dynamic capabilities on manufacturing firms’ performance have been minimal. The general objective of the study was to examine the influence of the three dimensions of dynamic capabilities (sensing capabilities, seizing capabilities and reconfiguration capabilities) on firm performance. The study was grounded on the Resource-Based View theory. An explanatory research design was used for the cross-sectional survey. Primary data was obtained from 271 out of 369 firms sampled from a population of 1,496 manufacturing firms in Nairobi County, Kenya, using a structured questionnaire instrument through drop and pick. The questionnaire was completed by the firms’ CEOs. Reliability and validity tests were carried out on the research instruments and study measures. Hypotheses were tested using regression analysis results, namely: - sensing capabilities (B=0.215, P<0.01), seizing capabilities (B=0.194, P<0.01) and reconfiguration capabilities (B=0.182, P<0.001). These three variables combined, contributed 25.9% (R2=0.259) of the variance in firm performance. The study concluded that deployment of dynamic capabilities has significant influence on firm performance.